The development of learning song-integrated module based on flipped learning model to improve self-regulated learning and cognitive learning outcome of junior high school students - Andreas Andreas; Risya Pramana Situmorang; Susanti Pudji Hastuti (Universitas Ahmad Dahlan, 2019)
The objectives of the research are to develop and produce a learning song-integrated module based on flipped learning model and to evaluate its effectiveness to improve student self-regulated learning and cognitive learning outcome. This development research is underpinned by Borg, W. R & Galls theory which has been modified into eight stages. Data collection techniques used were questionnaire, written test, and observation. During the development process, the data was analyzed using descriptive qualitative analysis, quantitative method and paired sample t-test. The results show that (1) the learning song-integrated module based on flipped learning model which was developed was feasible and effective to improve students self-regulated learning and cognitive learning outcome, 2) the learning song-integrated module based on flipped learning model about human digestive system material was feasible and effective in enhancing self-regulated learning and cognitive learning outcome of Grade VIII students of Grace Anak Terang Junior High School, Salatiga. The finding is supported by average percentage of self-regulated learning reaching 80% and cognitive learning outcome of students with a significance value of 0.00 < 0.05 (significance level 0.05) or 80.5%.